A Novel EDOT/F Co‐doped PMIA Nanofiber Membrane as Separator for High‐Performance Lithium‐Sulfur Battery. Issue 20 (19th September 2022) - Xiang, Hengying; Liu, Xia; Deng, Nanping; Cheng, Bowen; Kang, Weimin
Abstract: In this study, a novel fluorine‐containing emulsion and 3, 4‐ethylene dioxyethiophene (EDOT) co‐doped poly‐m‐phenyleneisophthalamide (PMIA) nanofiber membrane (EDOT/F‐PMIA), as the separator of lithium‐sulfur battery, was tactfully prepared via electrospinning. The multi‐scale EDOT/F‐PMIA nanofiber membrane can be served as the matrix to fabricate gel polymer electrolyte (GPE). Furthermore, under the influence of fluorine‐containing emulsion and EDOT, the PMIA‐based GPE possessed excellent thermostability, eminent mechanical property and well‐distributed lithium‐ions flux. Especially, the pore size of the nanofiber membrane decreased after adding the fluorine‐containing emulsion and EDOT. And the element S and O in EDOT with lone pair electrons were capable of binding with the lithium polysulfides, which was conducive to inhibiting the "shuttle effect" of lithium polysulfides by combining the physical confinement and chemical binding. Therefore, the lithium‐sulfur battery assembled with the EDOT/F‐PMIA separator exhibited excellent electrochemical performance, which delivered a high initial capacity of 851.9 mAh g −1 and maintained a discharge capacity of 641.1 mAh g −1 after 200 cycles with a capacity retention rate of 75.2% at 0.5 C. Abstract : Separator : Herein, the fluorine‐containing emulsion and 3, 4‐ethylene dioxyethiophene (EDOT) co‐doped poly‐m‐phenyleneisophthalamide (PMIA) nanofiber membrane, as the separator of lithium sulfur battery, is prepared via electrospinning. The PMIA‐based gel polymer electrolyte (GPE) can restrain the "shuttle effect" of lithium polysulfides by combining the physical confinement and chemical binding.